Processing Livestock Waste into Organic Fertilizer in the Kelompok Usaha Bersama (KUBE) Rare Angon Goat Farming in Temesi Village, Gianyar Regency - Mardewi, Ni Ketut; Tonga, Yan; Sutapa, I Gede; Natama, I Putu Ngurah; Pranamya, I Agus Karta; Koni, Mardiyanto Bora (PT FORMOSA CENDEKIA GLOBAL, 2024)
The community partnership program at Kelompok Usaha Bersama (KUBE) Rare Angon Goat Farming aims to increase the productivity of goat livestock to support livestock and agricultural businesses in partner groups, especially in terms of providing a technological touch in processing livestock and agricultural waste into solid and liquid organic fertilizer of high quality and economic value.Goat farming is one of the livestock commodities that produce meat and milk which has great potential to be developed Target What is achieved from the activity is that partners can look after goats well and can independently make quality organic fertilizers that have economic value. Apart from that, an increase in the economic value of livestock waste was also achieved by up to 20%. The able in this activity is This activity is also able to reduce environmental pollution by up to 40%